The challenges facing programs for the prevention and control of non-communicable diseases in Iran: a qualitative study of senior managers' viewpoints - Yegane Partovi; Mostafa Farahbakhsh; Jafar Sadegh Tabrizi; Kamal Gholipour; Ahmad Koosha; Jabreil Sharbafi; Andrew Wilson (BMC, 2022)
Abstract Background Despite significant achievements in the prevention and control of NCDs in Iran, these conditions are still the biggest challenges to Iran's healthcare system and are estimated to account for 78.1 percent of all deaths. Therefore, this study aimed to reflect on the potential challenges standing in the way to implement the relevant policies, empower the dimensions of governance, and react in an effective and timely manner by Iran's healthcare system to NCDs. Methods This study was conducted with a qualitative approach using the conventional content analysis method. A total of 46 senior managers involved in the prevention and control of NCDs at the medical sciences universities across Iran were recruited through the purposive sampling method and were interviewed via semi-structured interviews. Graneheim and Lundman's approach was utilized to analyze the data. Results According to the analysis of the senior managers' viewpoints, current challenges to implement the program for the prevention and control of NCDs in Iran could be placed into six main categories, including financing, human resources, infrastructure and inputs, legal, executive, administrative, as well as inter-sectoral collaboration, and management and policy-making challenges with their own sub-categories. Conclusion The results revealed that financing was the biggest challenge to successfully implementing the program for the prevention and control of NCDs in Iran. However, strengthening Iran's healthcare system in the field of the prevention of NCDs demanded more innovative measures and strategies, such as the empowerment of human resources, the effective use of intra- and inter-sectoral collaboration, and non-governmental organizations and charities, along with the exploitation of evidence-based studies during policy-making and decision-making processes, with no need for financial resources.